From divine timemaker to divine watchmaker: an exploration of God's temporality - Mullins, R. T. (Routledge studies in analytic and systematic theology, 2025)
"This book offers the most extensive exploration of divine temporality to date. It focuses on five main questions. First, what is time? Second, how is God responsible for the existence of time? Third, what does it mean to say that God is temporal? Fourth, what kind of structure might God give to a time series? Fifth, what are the implications for theological doctrines such as the Trinity, creation, providence, and life after death? The author offers a deep, critical engagement with the Christian tradition but also goes beyond to build analytic bridges to Jewish, Islamic, Hindu, and Jainist philosophical theology. The book provides an up-to-date discussion of issues within analytic metaphysics, philosophy of time, and philosophy of religion, and draws on the resources of contemporary systematic, historical, and biblical theology"--